Effect of intercropping Lolium perenne in Ziziphus jujuba orchards on soil quality in the canopy - Yao Ma; Bin Cao; Xiaojia Wang; Weijun Chen (PeerJ)
The cultivation of Lingwu jujube traditionally employs clean tillage, leaving substantial gaps between rows and exposing almost 60% of the orchard to the elements. This method promotes rapid soil moisture evaporation, exacerbates soil erosion, and deteriorates the soil’s physicochemical properties. Consequently, there is a critical need for a more sustainable planting approach that optimally utilizes land resources. A pertinent question is whether varying densities of ryegrass intercropping can improve the uptake of nutrients and water by the jujube tree, the primary species in this ecosystem. In this context, a 2-year field experiment was conducted with three densities of perennial ryegrass intercropped with Lingwu jujube. The experiment assessed the impact on soil’s physical and chemical attributes beneath the jujube canopy, with a focus on correlating soil moisture, enzyme activity, and physical properties. The findings reveal that intercropping at a medium density most effectively enhanced the soil’s physical characteristics. Relative to monoculture, this approach increased the proportion of water-stable aggregates (0.5–0.25 mm) by 4.16%, decreased the soil’s fractal dimension by 0.46%, augmented the field water holding capacity by 14.78%, and significantly boosted soil enzyme activity. Furthermore, high-density ryegrass intercropping elevated the soil’s organic matter content by 36.09% and ameliorated both the pH and cation exchange capacity. Conversely, low-density intercropping raised soil moisture levels by 40.18% in the top 20 cm of the soil. Collectively, these results suggest that an optimal density of ryegrass in intercropping not only bolsters the moisture retention capabilities of soil in Lingwu jujube orchards but also enhances overall soil fertility. Therefore, the adoption of ryegrass and jujube tree intercropping is highly advisable in the ecologically sensitive and resource-constrained arid sandy regions of northern China, offering substantial practical benefits.